Urgensi Supervisi Pendidikan di Sekolah - M Bustanul Ulum (STAIFAS-Press, 2018)
The quality of educational institutions is supported by several system elements including supervision of education carried out by principals as supervisors as mandated by Minister of National Education Regulation (Permendiknas) Number 13 of 2007 concerning Standard Principals who must supervise education in the form of supervision and assessment of teacher performance and employees who aim to assist teachers and employees in achieving educational goals starting from planning, implementation and evaluation to be optimal in carrying out institutional tasks in an organizational frame that leads to the quality of the institution. Educational supervision serves to coordinate all school efforts including all role holders in the school organization and broaden the experience through giving constructive criticism from the principal to teachers and employees. References to educational supervision include curriculum components, curriculum content and curriculum development strategies, improvement of teaching references in terms of making learning planning, optimizing the educational functions and educational goals embodied in the school's vision and mission. Keyword: Supervision of Education, Schools.